Improved Laboratory Enrichment for Enterohemorrhagic Escherichia coli by Exposure to Extremely Acidic Conditions - Grant, Michael A. (American Society for Microbiology, 2004)
Analysis of food samples for E. coli O157:H7 using the standard U.S. Food and Drug Administration procedure is frequently complicated by overgrowth of nontarget microorganisms. A new procedure was developed for enrichment of enterohemorrhagic E. coli (EHEC) which utilizes exposure to pH 2.00 for 2 h. This procedure yielded larger populations of EHEC than the standard method by factors ranging from 2.7 to 7.7 and, when age-stressed cultures were used, by factors ranging from 2.7 to 11.5. Cultures of competing enterics were more effectively inhibited by the new enrichment protocol as well.